2017
DOI: 10.1021/acs.jpclett.7b02709
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Quantitative Measurements of Paramagnetic Relaxation Enhancements in Cu(II)-Tagged Proteins by Proton-Detected Solid-State NMR Spectroscopy

Abstract: We demonstrate rapid quantitative measurements of site-resolved paramagnetic relaxation enhancements (PREs), which are a source of valuable structural restraints corresponding to electron-nucleus distances in the ~10–20 Å regime, in solid-state nuclear magnetic resonance (NMR) spectra of proteins containing covalent Cu2+-binding tags. Specifically, using protein GB1 K28C-EDTA-Cu2+ mutant as a model, we show the determination of backbone amide 15N longitudinal and 1H transverse PREs within a few hours of experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 38 publications
(123 reference statements)
0
7
0
Order By: Relevance
“…In a previous study, R 1 ( 1 H) or R 2 ( 1 H) PREs generated by a Mn 2+ -EDTA tag were shown to give good quality distances in the range between 16 and 23 Å . That same study also reported good quality distances from the same EDTA tag loaded with Cu 2+ in the range between 9 and 18 Å. Cu 2+ tags have also successfully been used for distance measurements in the solid state in the range between 11 and 19 Å, with limited accuracy. The data presented here allow more accurate distance measurements over a larger range than either of these transition metals. Furthermore, a high degree of accuracy is maintained for long distances, so that the useful range of distance measurements may extend beyond 23 Å in a larger protein complex.…”
Section: Discussionmentioning
confidence: 67%
“…In a previous study, R 1 ( 1 H) or R 2 ( 1 H) PREs generated by a Mn 2+ -EDTA tag were shown to give good quality distances in the range between 16 and 23 Å . That same study also reported good quality distances from the same EDTA tag loaded with Cu 2+ in the range between 9 and 18 Å. Cu 2+ tags have also successfully been used for distance measurements in the solid state in the range between 11 and 19 Å, with limited accuracy. The data presented here allow more accurate distance measurements over a larger range than either of these transition metals. Furthermore, a high degree of accuracy is maintained for long distances, so that the useful range of distance measurements may extend beyond 23 Å in a larger protein complex.…”
Section: Discussionmentioning
confidence: 67%
“…647 R 1 PREs of 1 H spins are challenging to measure in solids due to spin diffusion effects, but R 2 PREs of 1 H can offer long-range distance restraints. 648 R 2 PREs by the SBM mechanism are largest for paramagnetic centers with slowly relaxing electrons such as the nitroxide spin label, which has also been demonstrated in GB1 by ligating cysteine residues with MTSL. 649 Measurement of PCSs generated by paramagnetic metal tags is more difficult in solids than in solution, because different orientations of the metal complex relative to the protein would lead to a range of different PCSs.…”
Section: Biomolecules With Paramagnetic Tags In the Solid Statementioning
confidence: 78%
“…These measurements provide valuable information about amyloid structure, including data inaccessible by conventional SSNMR, and, remarkably, enable the determination of the protein fold in the huPrP23-144 amyloid core and protofilament assembly. This methodology is expected to be broadly applicable to other amyloid-forming proteins and can be further extended to other types of paramagnetic tags , and by incorporating rapid sample spinning and proton detection , for improved sensitivity.…”
mentioning
confidence: 99%